ESTIMATION OF LEAF-LITTER DECOMPOSITION RATE Avicennia sp. ON THE NUTRIENTS CONTENT IN WONOREJO MANGROVE AREA, SURABAYA - Hariyadi, Hariyadi; Hakim, Riza Rahman; Fitri, Ruhul Jihadil (Jurnal Perikanan Unram, 2025)
The ecosystems of mangrove are one of the unique coastal ecosystems which have ecological and socio-economic functions. Mangroves have a significant role in supporting fisheries resources. Leaf-litter is a nutrient contributor released to the sea water and is functioned by aquatic biota both in the marine and estuary. The method used in this study is purposive random sampling method which refer to the category based on mangrove density. The average production of mangrove litter Avicennia sp, for 30 days at station I was 1.04 g/m²/ day, station II was 1.20 g/m²/day, station III was 0.75 g/m²/day. The leaf-litter decomposition rate at station I, experienced a decomposition process of 65%, at station II at 62.33%, and station III at 69.42%. The content of nitrogen (N) and fosfor (P) nutrients at station I is an average of N 0.74% and P 0.07%, station II is N 0.76% and P 0.05%, station III is N 0.74% and P 0 , 07%. The total amount of nutrients released in the Mangrove Information Center forest area, Wonorejo - Surabaya is nitrogen (N) 443.81 kg/m²/year and phosphor (P) 34.103 kg/m²/year.